Wise Use of Social Media in National Defense - Ni Putu Widantari Suandana; Fachmi Hidayatulloh; I Putu Dharma Kusala; Tri Yovandi Kurniawan; Arti Amartya Pratiwi (Catuspata, 2022)
National defense is a reflection of the attitudes and actions of citizens based on love for the homeland. Social media makes all users have the ability to interact, participate, and share information. Social media not only contains information that is positively matter, but also contains information that is negatively matter, such as hoax and hate speech that can divide and become a threat to a country. Wisely in using social media, the most basic aspect that must be considered is how to communicate. Communicating in social must pay attention to several characteristics, namely, networks, information, archives, interactions, social stimulation, and user content. As a step in responding to threats that can occur due to misuse of social media, prevention efforts can be made, namely the use of social media wisely. There are several things that can be done in using social media wisely, namely: promoting ethics, filtering information, spreading positive content.